Waqf and sustainable development law: models of waqf institutions in the Kingdom of Saudi Arabia and Indonesia - Zawawi Zawawi; Yuli Yasin; Muhammad Irfan Helmy; Ali Ma’yuf; Agus Arwani (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2023)
This research aims to find out the regional waqf (endowment) and sustainable development models in the Kingdom of Saudi Arabia and Indonesia in terms of their laws, managements and investments. It uses a qualitative approach through observation, documentation and interviews with officials and those in charge of waqf from the Kingdom of Saudi Arabia and Indonesia. The data was then elaborated with expert opinions based on Herman Daly’s sustainable economic theory and John Locke’s theory of ownership and Islamic law theory (hifz al-mãl, himãyah al-bī‘ah and istiṣlãh). This study found that through the waqf system, the waqf institutions in the Kingdom of Saudi Arabia and Indonesia managed to reach certain achievements, namely good education, poverty reduction, hunger alleviation, and decent work. It was found that waqf institutions in the Kingdom of Saudi Arabia carried out various programs in every area of sustainable development, including providing drinking water. Another service included digging wells in areas where they were needed, which we rarely found in Indonesia. The Sustainable Waqf Law contributed to several aspects that could positively impact society and sustainable development in general. The Sustainable Waqf Law could positively impact sustainable social, economic, and environmental development. In addition, the waqf contributed to the United Nations Sustainable Development Goals No. 1, 2, 3, 4, 6, 11, 13 and 16. Finally, it is important to involve various parties, including waqf institutions, government, communities, and other stakeholders, to ensure the sustainability, transparency, and fairness in the management of waqf assets and their utilization in achieving sustainable development goals.